PENGUKURAN KINERJA KEUANGAN PT SARIGUNA PRIMATIRTA TBK DENGAN PENDEKATAN ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) - Retno Suwiyanti; Silva Savarin (Jurnal Aplikasi Perpajakan, 2026)
This study aims to analyze the financial performance of PT Sariguna Primatirta Tbk using the Economic Value Added (EVA) and Market Value Added (MVA) methods for the 2021–2024 period. A quantitative descriptive research method was employed, utilizing documentation and literature review techniques. The study relied on secondary data—specifically the annual financial statements of PT Sariguna Primatirta Tbk for 2021–2024—obtained from the company's official website and the Indonesia Stock Exchange. Data analysis involved calculating EVA based on the components of Net Operating Profit After Tax (NOPAT), Invested Capital, Weighted Average Cost of Capital (WACC), and Capital Charge, as well as calculating MVA based on the difference between the company's market value and the book value of equity. The results indicate that PT Sariguna Primatirta Tbk’s EVA was positive (EVA > 0) throughout the 2021–2024 period, signifying the company's ability to generate economic value added through its operations after accounting for the cost of capital. Furthermore, the MVA was also positive (MVA > 0) across the entire study period; this indicates that the company's market value exceeded its book value of equity, demonstrating success in creating value for shareholders.